ПЕДАГОГІЧНИЙ МОНІТОРИНГ ЯК ЕФЕКТИВНИЙ ІНСТРУМЕНТ ДІАГНОСТИКИ РОЗВИТКУ УЧНІВ В СИСТЕМІ ОСОБИСТІСНО-ОРІЄНТОВАНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2008)
In article pedagogical monitoring as the tool of diagnostics of development of pupils, and also the basic pedagogical conditions of his effective using in system of personality-oriented teaching are considered.